PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN RAWAT JALAN PENGGUNA KARTU BPJS DI PUSKESMAS KEDAWUNG 1 KABUPATEN SRAGEN - Wardani, Iin Fajar (JI@P, 2021)
The research purposes were: 1) determined the effect of tangibles, reliability, responsiveness, assurance, and emphaty on satisfaction of outpatient BPJS card users at Puskesmas Kedawung 1, Sragen Regency; and 2) determined the effect of service quality on satisfaction of outpatient BPJS card users at Puskesmas Kedawung 1, Sragen Regency. This is quantitative descriptive research. Research was conducted at Puskesmas Kedawung 1, Sragen Regency. Research sample was 50 outpatient who used BPJS cards who checked in August-September 2020 at Puskesmas Kedawung 1. Data collection techniques were used questionnaires, documentation, and literature study. Hypothesis testing were used multiple regression analysis, t test, F test, and coefficient of determination (R2). The results showed that 1) Tangibles, reliability,responsiveness, assurance and empathy have positive and significant effect on the satisfaction of outpatient BPJS card users at Puskesmas I Kedawung; and 2) Service quality has a positive and significant effect on the satisfaction of outpatient BPJS card users at Puskesmas I Kedawung.